Theophylline-encapsulated Nile Tilapia fish scale-based collagen nanoparticles effectively target the lungs of male Sprague–Dawley rats - Mohammed Moustapha Anwar; Manal Aly Shalaby; Hesham Saeed; Haitham Mohammed Mostafa; Dalia Galal Hamouda; Howaida Nounou (Scientific Reports, 2022)
Abstract Nile Tilapia fish scale collagen has high biodegradability, excellent biocompatibility, and low antigenicity. We assessed both the encapsulation efficiency of theophylline into Nile Tilapia fish scale-based collagen nanoparticles and their stability as a pulmonary drug delivery system in male Sprague–Dawley rats. The present study has demonstrated the successful encapsulation of theophylline into the synthesised nanoparticles as shown by spectrophotometric analysis, light microscope, scanning electron microscope, transmission electron microscope, and dynamic light scattering. The antibacterial activity of the nanoparticles improves with increasing their concentrations. Intratracheal treatment of rats using theophylline-encapsulated nanoparticles reduced the levels of creatinine, alanine transaminase, and aspartate transaminase, compared to the control group. Nevertheless, nanoparticles combined with theophylline exhibited no effects on cholesterol and triglycerides levels. Histopathological examination revealed typical uniform and diffuse thickening of the alveolar walls with capillary oedema in treated rats. We concluded that the synthesised collagen nanoparticles appropriately target the lungs of male Sprague–Dawley rats when delivered via a nebuliser, showing good tolerability to lung cells. However, dose ratio of collagen nanoparticles to theophylline needs further evaluation. The nanoprecipitation method may be optimised to involve poorly water-soluble inhaled drugs, and avoid the drawbacks of traditional drug delivery.